The Dissemination of Rift Valley Fever Virus to the Eye and Sensory Neurons of Zebrafish Larvae Is Stat1-Dependent - Sebastiaan ter Horst; Aleksandra Siekierska; Ann-Sofie De Meulemeester; Arno Cuvry; Laura Cools; Johan Neyts; Peter de Witte; Joana Rocha-Pereira (Viruses)
The Rift Valley fever virus (RVFV) causes haemorrhagic fever, encephalitis, and permanent blindness and has been listed by the WHO as a priority pathogen. To study RVFV pathogenesis and identify small-molecule antivirals, we established a novel In Vivo model using zebrafish larvae. Pericardial injection of RVFV resulted in ~4 log10 viral RNA copies/larva, which was inhibited by the antiviral 2′-fluoro-2′-deoxycytidine. The optical transparency of the larvae allowed detection of RVFVeGFP in the liver and sensory nervous system, including the optic tectum and retina, but not the brain or spinal cord. Thus, RVFV-induced blindness likely occurs due to direct damage to the eye and peripheral neurons, rather than the brain. Treatment with the JAK-inhibitor ruxolitinib, as well as knockout of stat1a but not stat1b, enhanced RVFV replication to ~6 log10 viral RNA copies/larva and ultra-bright livers, although without dissemination to sensory neurons or the eye, thereby confirming the critical role of stat1 in RVFV pathogenesis.